Development of tri hita karana based e-modules in strengthening pancasila student profiles - Faradisa, Nuril; Mudana, I Wayan; Wesnawa, I Gede Astra (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This study aims to practicality, and effectiveness of tri hita karana based e-modules in strengthening the profile of Pancasila students at SMP Negeri 2 Singaraja. The type of research used is research and development (R&D) with a mixed method approach. The research was conducted at SMP Negeri 2 Singaraja. The sample was determined using a random sampling technique with class VII-1 as the research sample. The data collection technique uses observation, interview, questionnaire, and documentation techniques. The data were analyzed using qualitative descriptive techniques. The practicality of the e-module teaching materials in the category is very practical through the practicality test of teachers and students with very good results The e-module teaching materials are effective in improving the profile of Pancasila students at SMP Negeri 2 Singaraja